Anti-proliferative and anti-inflammatory eudesmanolides from the flowers of Sphagneticola trilobata (L.) Pruski. (June 2023) - Zhang, Bei; Wang, Lutong; Wang, Lin; Wang, Yihai; Xu, Jingwen; He, Xiangjiu
Abstract: Twenty-six eudesmanolides including six undescribed compounds were isolated from the flowers of Sphagneticola trilobata (L.) Pruski. Their structures were elucidated based on the interpretation of spectroscopic techniques, NMR calculation, and DP4+ analysis. The stereochemistry of (1 S, 4 S, 5 R, 6 S, 7 R, 8 S, 9 R, 10 S, 11 S )-1, 4, 8- trihydroxy-6-isobutyryloxy-11-methyleudesman-9, 12-olide (1 ) was demonstrated by single crystal X-ray diffraction. All eudesmanolides were evaluated for their anti-proliferative activities against four human tumor cell lines (HepG2, HeLa, SGC-7901, and MCF-7). 1 α, 4 β -Dihydroxy-6 α -methacryloxy-8 β -isobutyryloxyeudesman-9, 12-olide (3 ) and wedelolide B (8 ) showed pronounced cytotoxic effects against AGS cell line with IC50 values of 1.31 and 0.89 μM, respectively. Their anti-proliferative activities against AGS cells were exerted through a dose-dependent apoptosis pathway, as verified by cell and nucleus morphological assessment, clone formation assay, and Western blot analysis. Furthermore, 1 α, 4 β, 8 β -trihydroxy-6 β -methacryloxyeudesman-9, 12-olide (2 ) and 1 α, 4 β, 9 β -trihydroxy-6 α -isobutyryloxy- 11 α -13-methacryloxyprostatolide (7 ) performed significant inhibitory effects on lipopolysaccharide-stimulated nitric oxide production in RAW 264.7 macrophages with IC50 values of 11.82 and 11.05 μM, respectively. Moreover, compounds 2 and 7 could block the nuclear translocation of NF- κ B and reduce the expression of iNOS, COX-2, IL-1 β, and IL-6 to exert anti-inflammatory effects. This study provides evidence for the utilization of the eudesmanolides from S. trilobata as lead compounds for further research due to their cytotoxic potential. Graphical abstract: Twenty-six eudesmanolides including six undescribed compounds were isolated from the flowers of Sphagneticola trilobata (L.) Pruski. Some eudesmanolides exhibited pronounced anti-inflammatory and anti-proliferative activities. Image 1 Highlights: Six undescribed eudesmanolides were isolated from Sphagneticola trilobata (L.) Pruski. Some eudesmanolides showed anti-proliferative and anti-inflammatory activities. The possible mechanisms of anti-proliferation and anti-inflammation were studied.